2007
DOI: 10.1073/pnas.0609833104
|View full text |Cite
|
Sign up to set email alerts
|

Selective defect of in vivo glycolysis in early Huntington's disease striatum

Abstract: Activity of complexes II, III, and IV of the mitochondrial electron transport system (ETS) is reduced in postmortem Huntington's disease (HD) striatum, suggesting that reduced cerebral oxidative phosphorylation may be important in the pathogenesis of neuronal death. We investigated mitochondrial oxidative metabolism in vivo in the striatum of 20 participants with early, genetically proven HD and 15 age-matched normal controls by direct measurements of the molar ratio of cerebral oxygen metabolism to cerebral g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
153
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(161 citation statements)
references
References 42 publications
(56 reference statements)
7
153
0
1
Order By: Relevance
“…In these individuals blood flow was 54 ml·g Ϫ1 ·min Ϫ1 in the evening before sleep, a value significantly higher (17%) than that obtained the following morning. However, it should be noted that the value they obtained in the evening was within the range of normal values obtained in humans without regard to the time of day (e.g., see Kety and Schmidt 1948;Powers et al 2007;Raichle et al 1970). The authors suggested this difference could be due to increases in blood flow due to sleep deprivation or a decrease brought about by intervening "recovery sleep" (or both).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these individuals blood flow was 54 ml·g Ϫ1 ·min Ϫ1 in the evening before sleep, a value significantly higher (17%) than that obtained the following morning. However, it should be noted that the value they obtained in the evening was within the range of normal values obtained in humans without regard to the time of day (e.g., see Kety and Schmidt 1948;Powers et al 2007;Raichle et al 1970). The authors suggested this difference could be due to increases in blood flow due to sleep deprivation or a decrease brought about by intervening "recovery sleep" (or both).…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, it has been tacitly assumed by most that the consumption of glucose and oxygen represents the brain's need for energy without consideration of possible additional roles. However, we know that glucose consumption exceeds that needed for oxidative phosphorylation by about 15% in the resting adult human (Powers et al 2007;Raichle et al 1970). This has traditionally been referred to as aerobic glycolysis (i.e., glucose consumption occurring in excess of that needed for oxidative phosphorylation in the presence of adequate tissue oxygenation).…”
Section: Discussionmentioning
confidence: 99%
“…Modified glycolytic energy metabolism has been described in HD patients, both in central and in peripheral tissues, as suggested by high levels of lactate in the striatum (Jenkins et al, 1993) and in the cortex (Jenkins et al, 1993;Koroshetz et al, 1997), increased lactate/ pyruvate ratio in the CSF (Koroshetz et al, 1997), but decreased astrocytic glucose metabolism in the striatum with preserved oxygen metabolism in early symptomatic HD patients (Powers et al, 2007b). Moreover, the activity of G6PD, a key enzyme of the pentose phosphate pathway, was decreased in HD cybrids, suggesting that glucose metabolization occurs through the glycolytic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…HD patients present high levels of lactate in both the striatum (Jenkins et al, 1993) and cortex (Jenkins et al, 1993;Koroshetz et al, 1997), and increased lactate/pyruvate ratio in the cerebrospinal fluid (CSF) (Koroshetz et al, 1997). Striatal glucose metabolism was also shown to be decreased, whereas oxygen metabolism is preserved in early symptomatic HD patients (Powers et al, 2007b). Moreover, increased glucose metabolism and ATP levels were found in brain tissue of HD N171-82Q mice, suggesting that the neuronal damage in HD tissue may be associated with increased energy metabolism at the tissue level, leading to modified levels of various intermediary metabolites (Olah et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…During HD, an increased ratio of the cerebral metabolic rate of oxygen consumption to glucose consumption is an indication of an impairment in glycolysis. 39 Furthermore, the selective inhibition of glycolysis with iodoacetate increases the susceptibility of medium spiny neurons to excitotoxic cell death in the R6/2 transgenic mouse model of HD. 40 All of these properties seen in medium spiny neurons point to a neuron type that is energetically unique in the brain: a strong dependence on oxidative metabolism and glycolysis to cope with the high energy demands as a result of its connectivity.…”
Section: The Differential Expression Of the Ck Isozymes Is Also Apparmentioning
confidence: 99%